2021
DOI: 10.1088/1361-6587/abdcdd
|View full text |Cite
|
Sign up to set email alerts
|

Plasma rotation driven by rotating magnetic fields

Abstract: We report a novel method to control plasma rotation speed, namely, using the rotating magnetic field (RMF), which is a mature technique to form field reversed configuration, to drive the electron rotation and then the ion rotation via electron–ion collisions in a magnetic mirror plasma. It can be observed that the plasma starts rotating if the RMF strength exceeds a threshold value, corresponding to which the value of the magnetization parameter becomes larger than the value of the penetration parameter. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A better result could be achieved if the initiate plasma in KMAX can be better, for instance, better ionization or less neutrals. In a separate experiment, the RMF was relocated to the central cell, and it was found that the RMF can rotate the plasma and create a shear flow [38]. The triple probe measurements reveals that the plasma density profile becomes more peaked, indicating a change in the radial transport.…”
Section: Simulations and Experimentsmentioning
confidence: 96%
“…A better result could be achieved if the initiate plasma in KMAX can be better, for instance, better ionization or less neutrals. In a separate experiment, the RMF was relocated to the central cell, and it was found that the RMF can rotate the plasma and create a shear flow [38]. The triple probe measurements reveals that the plasma density profile becomes more peaked, indicating a change in the radial transport.…”
Section: Simulations and Experimentsmentioning
confidence: 96%
“…The KMAX θ-pinch FRC is an FRC experiment with θ-pinch coils installed inside the central cell of a tandem mirror device named KMAX (Keda Mirror with AXisymmetry) [12,13]. As depicted in figure 1(a), KMAX is at present a 10.4 m long axisymmetric tandem mirror device primarily comprising one central cell and two end cells, which are 5.2 m and 2.2 m in length, respectively [14]. The diameters of the central vessel and the mirror throat are 1.2 m and 0.3 m, respectively.…”
Section: Kmax θ-Pinch Frcmentioning
confidence: 99%
“…The experiments were conducted on KMAX-FRC [25]. KMAX θ-pinch FRC is an FRC experiment with θ-pinch coils installed inside the central cell of an axisymmetric tandem mirror device named KMAX [26][27][28]. As depicted in figure 1(a), KMAX has a total length of ∼11 m, which is primarily comprised of one central cell, two side cells, and two end chambers.…”
Section: Keda Mirror With Axisymmetry (Kmax)-frcmentioning
confidence: 99%